THE INFLUENCE OF SERVICE AND PRODUCT VARIANTS ON CUSTOMER LOYALTY OF ADL GROCERY STORES ON PAJENEKANG ISLAND - Ari darni latif; Agus Syam; Sumiati Tahir; Muhammad Rakib; Nur Halim (Adisam Publisher, 2025)
The purpose of this research is to determine the influence of service and product variants on customer loyalty at the Adl Grocery Store on Pajenekang Island. The independent variable in this research is the influence of service and product variants, while the dependent variable is customer loyalty. The population in this study was all 325 residents of Pajenekang Island. Meanwhile, the sample in this study was 65 respondents using random sampling techniques. Data collection was carried out by distributing a list of questions (questionnaires) to respondents. The data analysis technique used was multiple regression analysis using SPSS software. Based on the results of the analysis and discussion, it can be concluded that: The service influence variable (X1) has a partial influence on the dependent variable, namely the customer loyalty variable (Y). Furthermore, the product variant variable has a partial influence on the variable, namely customer loyalty (Y). the same (Simultaneous) effect on the dependent variable, namely Customer Loyalty (Y).